Adaptive nonlinear robust relative pose control of spacecraft autonomous rendezvous and proximity operations. (March 2017) - Sun, Liang; Huo, Wei; Jiao, Zongxia
Abstract: This paper studies relative pose control for a rigid spacecraft with parametric uncertainties approaching to an unknown tumbling target in disturbed space environment. State feedback controllers for relative translation and relative rotation are designed in an adaptive nonlinear robust control framework. The element-wise and norm-wise adaptive laws are utilized to compensate the parametric uncertainties of chaser and target spacecraft, respectively. External disturbances acting on two spacecraft are treated as a lumped and bounded perturbation input for system. To achieve the prescribed disturbance attenuation performance index, feedback gains of controllers are designed by solving linear matrix inequality problems so that lumped disturbance attenuation with respect to the controlled output is ensured in the L 2 -gain sense. Moreover, in the absence of lumped disturbance input, asymptotical convergence of relative pose are proved by using the Lyapunov method. Numerical simulations are performed to show that position tracking and attitude synchronization are accomplished in spite of the presence of couplings and uncertainties. Abstract : Highlights: A nonlinear coupled 6-DOF relative pose model is formulated for the chaser approaching to the disturbed and uncontrolled target. Spacecraft relative position tracking and attitude synchronization are addressed. An adaptive robust nonlinear disturbance attenuation controller with proportional-integral-derivative structure is proposed. The capabilities of the control scheme are demonstrated by experimental simulations.